Mining flies of the subfamily Agromyzinae (Diptera, Agromyzidae) of Ukrainian Transcarpathia with the description of three new species - Guglya, Yu. (Zoodiversity, 2020)
Based on the material recently collected in the Transcarpathian Ukraine, three previously unknown species of the mining flies are described: Ophiomyia kireshii sp. n., O. mukhorytsa sp. n. and Agromyza paralucida sp. n. Heads, wings, male and female terminalia are illustrated and DNA sequences of the new species are provided. In addition, five species previously unknown to occur in Ukraine were found and added on the list of Ukrainian Agromyzidae: Melanagromyza nartschukae Pakalniškis, 1996, Ophiomyia pseudonasuta Černý, 1994, Agromyza anderssoni Spencer, 1976, A. hendeli Griffiths, 1963, and A. lucida Hendel, 1920. All species go with short general data on their distribution in Ukraine and rare species are provided with detailed distribution information that not listed earlier. The number of confirmed Ukrainian Agromyzinae species is now 105.